Growth Response of Lime (Citrus Aurantifolia) Cuttings at Origin Different Parts of Cuttings and Providing Natural ZPT on Shallots - Turi Handayani; Rita Mawarni CH; Heru Gunawan; Andri (Kirana Publisher (KNPub), 2023)
This research was carried out in Binjai Serbangan, Air Joman District, Asahan Regency. The research was carried out from February to May 2022. The aim of the research was to determine the response of the growth of citrus cuttings to the origin of different cuttings and the natural ZPT of shallots. This research used a factorial randomized block design (RAK) with two factors, namely: (1) Origin of cuttings (A) consisting of 3 levels, namely: A1 = shoot part, A2 = middle part, A3 = base part (2) Onion Extract Red (B), namely: B0 = 0%, B1 = 25%, B2 = 50%, B3 = 75%. The observation parameters carried out were the percentage of growth, age at emergence of shoots, number of shoots, height of shoots. The results showed that the origin of the cuttings had a significant effect on the number of shoots and shoot height at 6 mst. But on the percentage of growth, the age at which shoots appeared had no significant effect. The best treatment is in A2 = middle part. The concentration of shallot extract had a significant effect on the height of shoots aged 6 WAP. However, the percentage of growth, the age at which shoots appeared and the number of shoots had no significant effect. The best treatment is B3 = 75%. The interaction between the origin of the cuttings and the concentration of shallot extract had no significant effect on all parameters.